2023
DOI: 10.1002/hbm.26217
|View full text |Cite
|
Sign up to set email alerts
|

Changes in white matter microstructure following serial ketamine infusions in treatment resistant depression

Abstract: Ketamine produces fast‐acting antidepressant effects in treatment resistant depression (TRD). Though prior studies report ketamine‐related changes in brain activity in TRD, understanding of ketamine's effect on white matter (WM) microstructure remains limited. We thus sought to examine WM neuroplasticity and associated clinical improvements following serial ketamine infusion (SKI) in TRD. TRD patients ( N = 57, 49.12% female, mean age: 39.9) received four intravenous ketamine infusions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Lastly, there was no main effect of ketamine on ∆-MD, as we might predict if it were the sole mediator of treatment response, indicating that numerous other factors are likely involved in the antidepressant effects of ketamine among human patients. Such factors could include additional neuroplasticity mechanisms, such as the impact of ketamine on white matter microstructure and tractography [ 62 , 63 ] which was not assessed in the current study due to scanner sequence timing constraints and lack of a priori hypotheses regarding white matter effects; as well as a wide range of factors beyond neuroplasticity per se.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, there was no main effect of ketamine on ∆-MD, as we might predict if it were the sole mediator of treatment response, indicating that numerous other factors are likely involved in the antidepressant effects of ketamine among human patients. Such factors could include additional neuroplasticity mechanisms, such as the impact of ketamine on white matter microstructure and tractography [ 62 , 63 ] which was not assessed in the current study due to scanner sequence timing constraints and lack of a priori hypotheses regarding white matter effects; as well as a wide range of factors beyond neuroplasticity per se.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who met DSM-5 diagnostic criteria for MDD ( 25 ) and experienced inadequate response to 2 or more prior antidepressant trials of sufficient dose and duration and had been continuously depressed for at least 6 months were recruited. Further details on inclusion and exclusion criteria have been previously described ( 22 , 26 , 27 ). Briefly, inclusion criteria entailed men and women between the ages of 20–64, pre-treatment moderate to severe depressive symptoms (17-item Hamilton Depression Rating Scale (HDRS) total score ≥ 17), stable antidepressant or mood stabilizer use for 6 or more weeks prior to study participation.…”
Section: Methodsmentioning
confidence: 99%
“…However, alterations in visual networks have also been associated with depression 79,80 . Further, three studies from our own group employing different imaging modalities and including an overlapping TRD sample have reported ketamine-related modulation of visual areas, including changes in BOLD activation during a response inhibition task 81 , increases in cerebral blood flow 82 , and changes in white matter microstructure within occipital white matter pathways 83 . Notably, one of the few published studies investigating the effects of ketamine on habenula FC found that increases in sFC between the habenula and occipital pole and lateral visual cortex following a single ketamine infusion significantly correlated with improvements in subjectively rated depressive symptoms 50 .…”
Section: Discussionmentioning
confidence: 99%
“…However, alterations in visual networks have also been associated with depression 79,80 . Further, three studies from our own group employing different imaging modalities and including an overlapping TRD sample have reported ketamine-related modulation of visual areas, including changes in BOLD activation during a response inhibition task 81 , increases in cerebral blood flow 82 , and changes in white matter microstructure within occipital white matter pathways 83 .…”
Section: Effect Of Treatment On Hb and Nac Fcmentioning
confidence: 99%